A review on the assessment of plasticiser leaching from polyvinyl chloride and its prevention methods / Siti Nor Din, Aula Aqila Yusrizal, Dalina Samsudin and Faiezah Hashim - Din, Siti Nor; Yusrizal, Aula Aqila; Hashim, Faiezah (Universiti Teknologi MARA Shah Alam, 2023)
The production of the polyvinyl chloride (PVC) products is growing worldwide due to its high versatility and relatively low cost. However, PVC requires for plasticiser in order to improve its workability and flexibility to suit many applications area. The incorporation of plasticisers nevertheless comes with principle disadvantage which is the leaching out of the plasticisers used. Therefore, this review presents an overview of the leaching behaviour of plasticisers particularly for phthalate and natural-based plasticisers. Due to the problems that arise when leaching of plasticiser occurs, several methods to study the plasticiser leaching was elaborated which are Fourier transform infrared spectroscopy (FTIR), gas chromatography (GC), differential scanning calorimetric analysis (DSC), and migration stability test method. The results indicated that the leaching of the plasticisers could be identified by considering the loss of infrared characteristic band of plasticiser in the sample, retention time (tR) level, glass transition temperature (Tg) level and weight change when using the methods mentioned above, respectively. Moreover, two widely used surface treatment methods to prevent plasticiser leaching which are plasma treatment and ultraviolet (UV) irradiation are also being provided. However, these two methods cannot fully suppress the migration of plasticiser especially plasticiser having a lower molecular weight as it is highly volatile and difficult to control. Therefore, there is a need for more crucial studies in designing the best treatment method for the bright future of zero migration of plasticisers to enhance the use of PVC applications.